Model Simulasi Pengendalian Suhu Udara Pada Mesin Pengering Cabe Dengan Kontrol Logika Fuzzy - Argo, Bambang Dwi; Rahayu, Cicik (Fakultas Teknologi Pertanian Universitas Brawijaya, 2004)
The experiment is aimed to develop a model to control the air temperature of drying chamber during drying of Chilli using Logical Fuzzy Control (LFC). The temperature characteristic of three dryer subsystem, namely the drying chamber, the commodity (chilli), and the heater, is predicted by a mathematical models based on heat and mass balances. Mathematical model obtained were then solved by numerical analysis using a Finite Different Euler Method, followed by simultaneous solution by a method of Gauss Jordan. Borland Delphi 5.0 program and Celeron 566 MHz and RAM 256 MB processor was used to make a simulation program. The control of drying chamber temperature is carried out by adjustment of the energy given to the heater. The degree of deviation to the set temperature of the drying chamber and the corrected value were then used as inputs to LFC. As an output of the LFC is the amount of energy supplied to the heater. The input was divided into three groups of set i.e. 3.5 and 7. The function of the input element is a symmetrical triangle function, while the one of the output element is a fuzzy singletone. It was found that the determination value (R2) of the drying chamber, the commodity and the heater were 0.65, 0.62 and 0.67 respectively with the respective RMSE value of 2.2, 2.8 and 2.3. A set of input of 7 was found to give the best LFC as compared with other sets of input. The control of drying chamber temperature using LFC for drying of chilli is best conducted in the range of set point of 45 – 55 oC. At a temperature of 45 oC for 72 hours, the moisture content of the chilli was reduced from about 80 % to 32.9 % wet basis with an consumption of energy of 547.02 kWh. Keywords: Simulation, Logical Fuzzy Control, Finite Different Method, Gauss Jordan Method